2014
DOI: 10.1128/iai.01668-13
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via Tumor Necrosis Factor Receptor 1 but Not Toll-Like Receptor 2 Contributes Significantly to Hydrosalpinx Development following Chlamydia muridarum Infection

Abstract: Chlamydial infection in the lower genital tract can lead to hydrosalpinx, which is accompanied by activation of both pattern recognition receptor TLR2-and inflammatory cytokine receptor TNFR1-mediated signaling pathways. In the current study, we compared the relative contributions of these two receptors to chlamydial induction of hydrosalpinx in mice. We found that mice with or without deficiencies in TLR2 or TNFR1 displayed similar time courses of live organism shedding from vaginal swabs, suggesting that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…Since Ͼ50% of the mice were induced to develop uterine horn dilation by C. muridarum infection and none of the uninfected mice developed any significant uterine dilation, we concluded that the uterine horn dilation was induced by C. muridarum infection. The hydrosalpinx from the same set of mice was also noted, and some of the results were previously published (8,15,26,28,41). Although mice with more severe uterine horn dilation seemed to lack hydrosalpinx in the oviduct in some cases, there was no significant correlation between uterine horn dilation and oviduct hydrosalpinx when all 88 mice were taken into consideration.…”
Section: Muridarum Induces Uterine Horn Dilation In Mice Followingmentioning
confidence: 81%
See 2 more Smart Citations
“…Since Ͼ50% of the mice were induced to develop uterine horn dilation by C. muridarum infection and none of the uninfected mice developed any significant uterine dilation, we concluded that the uterine horn dilation was induced by C. muridarum infection. The hydrosalpinx from the same set of mice was also noted, and some of the results were previously published (8,15,26,28,41). Although mice with more severe uterine horn dilation seemed to lack hydrosalpinx in the oviduct in some cases, there was no significant correlation between uterine horn dilation and oviduct hydrosalpinx when all 88 mice were taken into consideration.…”
Section: Muridarum Induces Uterine Horn Dilation In Mice Followingmentioning
confidence: 81%
“…The following strains of wild-type and knockout (KO) mice used in the current study were all purchased from Jackson Laboratories (Bar Harbor, ME): C57BL/6J (JAX [Jackson Laboratories] stock number 000664), BALB/cJ (000651), C3H/HeJ (000659), TRIF KOs (005037), TIRAP KOs (017629), JNK2 KOs (004321), interleukin 1 receptor type I (IL-1R1) KOs (003245), IL-10 KOs (002251), and gamma interferon (IFN-␥) KOs (002287; 2 died before sacrifice). The pathology data for the remaining strains of mice used in the current study were acquired from the images and/or tissues of mice sacrificed in previous studies (8,15,24,26,28,41). The infection procedures were as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular basis for this attenuation is unclear but could involve plasmid-regulated genes (13) that function as Toll-like receptor 2 (14) or tumor necrosis factor alpha (TNF-␣) receptor antagonists (15,16). On the other hand, the basis of plasmid-mediated pathology might be a direct host-pathogen relationship caused by infection with virulent plasmid-bearing organisms.…”
mentioning
confidence: 99%
“…Thus, intravaginal inoculation of mice with C. muridarum has been used to study the mechanisms of C. trachomatis pathogenesis and immunity (3,(5)(6)(7). We recently optimized the C. muridarum mouse model by visually detecting long-lasting hydrosalpinges 8 weeks after infection (8)(9)(10)(11)(12). The C. muridarum murine model-based studies have led us to hypothesize that both adequate ascension to and induction of the appropriate inflammatory responses in the upper genital tract (UGT) are necessary for hydrosalpinx development.…”
mentioning
confidence: 99%